Responsibility of Central Banks for Stability in Financial Markets - Schinasi, Garry (IMF Working Papers; Working Paper, 2003)
What is the role of central banks in ensuring financial stability? This paper addresses this controversial subject, in part by drawing on the experiences in Europe, Japan, and the United States, and by examining four questions. What is meant by financial stability? Do central banks have a natural role in ensuring financial stability? What does a central bank need to execute this role effectively? How far have central banks actually gone in safeguarding financial stability? The experience drawn on in the paper suggest that central banks: have a natural role to play; at times may require supervisory information to execute this natural role; and have incurred risks to their balance sheets to ensure financial stability.